Spatial distribution of natural enrichments of Arsenic, Selenium, and Uranium in a minerotrophic peatland, Gola di Lago, Canton Ticino, Switzerland - González Acevedo, Zayre I.; Krachler, Michael; Cheburkin, Andriy K.; Shotyk, William (Environmental science & technology, 2006)
Gola di Lago is a small (ca. 3 ha), minerotrophic peatland in Canton Ticino, southern Switzerland. Chemical analyses of peat show remarkable concentrations of As, Se, and U. Coring at regular intervals (19 sites) revealed several zones of pronounced accumulation, with As concentrations up to 350 mg kg-1 (2000 mg kg-1 on a mineral matter basis). Both Fe and S are also enriched at this depth, suggesting that redox-related transformations have affected all three elements. High concentrations of Se (up to 28 mg kg-1) and U (up to 470 mg kg-1) were also detected, representing on a mineral matter basis 350 and 2900 mg kg-1, respectively. An intermittent stream entering the peatland contained up to 400 μg of As L-1, but the permanent stream leaving the mire contains <2 μg L-1. A three-dimensional map of the spatial distribution of As shows that the main source of As is the intermittent stream and not the basal, mineral sediment underlying the peatland. Arsenic is highly enriched not only in shallow peat layers at the interface between the stream and peatland today but also in deeper peat layers in the center of the mire, at what must have been the stream−peat interface in the past. By sequential extraction of fresh peat samples, 100% of the As could be extracted from a shallow sample but only 19% from a sample taken from the deeper layers. In both cases, most of the As was associated with the organic matter fraction (73% and 57% respectively). Although this peatland is an effective geochemical trap for As in the stream waters, the mechanisms of removal remain unclear.
Gesehen am 28.09.2020